Landasan Religi dan Nilai-Nilai Tujuan Pendidikan - Huda, Ali Anhar Syi'bul; Mukarrami , Nur Fadhillah; Supriadi , Udin; Nurhuda , Abid; Lathif , Nur Muhammad (Lembaga Einstein College (LEC), 2024)
This article attempts to reveal theoretically the meaning of foundation, religion, religious foundation, and values of educational objectives with the basic assumptions 1) related to foundation, religion, and religious foundation, and 2) the values contained in educational objectives, especially national education in Indonesia. The method used in writing this article uses a qualitative approach with library study methods and available data analysis techniques, namely descriptive. It was revealed that there is a common thread between the religious foundation and the spirit of the identity of the Indonesian nation, which recognizes Allah as God (worship) and is then manifested and reflected through Law No. 20 of 2003 concerning the National Education System of the Indonesian nation. The first thing mentioned is the divine aspect. So it would be very strange if there were institutions or individuals who were allergic to aspects of religion, so there is a need for self-evaluation and further study regarding national identity based on Pancasila.